Pentahelix Analysis dalam Program Kampung Iklim (Proklim) di Kelurahan Ditotrunan Kabupaten Lumajang - Alnizar Zagarino; Kalvin Edo Wahyudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Climate Village Program (Proklim) in Ditotrunan Village is a strategic effort to increase public awareness of the importance of preserving the environment through climate change adaptation and mitigation. This research aims to analyze the role of various stakeholders including academics, businesses, communities, government, and media in making people aware of environmental preservation through the implementation of Proklim. The research method used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that academics play a very good role through the Community Service Program (KKN), such as the creation of a Sustainable Food Yard (P2L) and an information board “The Length of Waste Decomposed”, which directly increases community understanding. The business sector contributes quite well through the culinary tourism initiative “doDolan Kampung” with the use of environmentally friendly packaging, while empowering the economy of the local community. Communities, such as Environmental Cadres and Youth Organizations, play an excellent role in encouraging active community participation through socialization and concrete actions. The government provides strong support through regulations and technical assistance. However, the role of the media is still limited due to the lack of collaboration in reporting, although there has been coverage from Kompas TV on environmental transformation in Ditotrunan. The conclusion of this study states that the implementation of Proklim in Ditotrunan Village has been going well with the support of stakeholders, although it needs to optimize the role of the media to expand the impact of socialization.